Othello Game Application Design Using Heuristic Techniques - Leo Benny; Lusi Herlina (Institute of Computer Science (IOCS), 2022)
Othello is a popular board game and is played by two players. Problems arise when there are no friends to play with or the player does not have a game device. To solve this problem, an Othello game application can be developed, so that players can play Othello against the computer. Research applies heuristic techniques in the game Othello. The heuristic technique calculates the number of player chips (points) that the computer can turn over on each tile or square. This number of points is then multiplied by the coefficient value of 1.5 if the square is on the side of the game, while the points obtained from the box in the corner of the board are multiplied by the coefficient value of 3. In the end, the computer will choose the box with the highest heuristic value. Thus, the heuristic technique will prioritize the placement of the pieces in the corner of the board, the side of the board and then the placement of the pieces in the middle of the board. The application applies artificial intelligence to the computer by using heuristic techniques, so that the computer will prioritize the placement of chips at the corners and edges of the board whenever possible.